Saving Seeds, Preserving Taste : Heirloom Seed Savers in Appalachia - Best, Billy F., 1935- (Book collections on Project MUSE., 2013)
The Brown Goose, the White Case Knife, Ora's Speckled Bean, Radiator Charlie's Mortgage Lifter?-?these are just a few of the heirloom fruits and vegetables you'll encounter in Bill Best's remarkable history of seed saving and the people who preserve both unique flavors and the Appalachian culture associated with them. As one of the people at the forefront of seed saving and trading for over fifty years, Best has helped preserve numerous varieties of beans, tomatoes, corn, squashes, and other fruits and vegetables, along with the family stories and experiences that are a fundamental part of th.